Diseño e implementación del control de un robot mediante el uso de dispositivos móviles (2015)
The degree project called ECIBotics, was proposed in order to bring the theory of computer programming, infrastructure and computing seen throughout the race with practical applications of control and improvement of the capacities given to electronic devices, susceptible to its control; for this purpose we use one of the devices, which has revolutionized the academy and has given a new air to the technology enthusiasts so that they can experiment and make their imagination fly, for a low price, this device is the computer of small format called Raspberry Pi. Within the process of improvement and control of a device it is necessary to introduce a Raspberry Pi, this reduced plate computer will function as the main brain of the device we want to control.